DEVELOPMENT OF AN ISLAMIC EDUCATION MODULE BASED ON THE LOCAL WISDOM OF THE EMBUHANGA COAST TO STRENGTHEN ENVIRONMENTALLY CONSCIOUS MORAL CHARACTER AMONG STUDENTS AT MI MUHAMMADIYAH EMBUHANGA - Fachrul Rozi Sasikome (As-Sulthan Journal of Education, 2026)
This study aims to develop an Islamic Religious Education (PAI) module based on the local wisdom of the Embuhanga coast to strengthen environmentally conscious moral character among students at MI Muhammadiyah Embuhanga. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants of the limited trial consisted of 11 students. Data were collected through observation, expert validation sheets, practicality questionnaires, and pretest-posttest assessments. The validation process involved a material expert and a media expert. The results showed that the module obtained feasibility scores of 30% for content, 40% for language, 60% for presentation, and 50% for graphics, with an overall average of 45%, categorized as adequate but requiring revision. The practicality results ranged from 50%–70%, indicating that the module was fairly practical for classroom use. Furthermore, the effectiveness test demonstrated an increase in students’ environmental ethics scores from 50 in the pretest to 70 in the posttest. The findings indicate that the developed module has the potential to become contextual teaching material in coastal madrasahs by integrating Islamic values with environmental awareness through local wisdom.